Людина і природа в науковій концепції Івана Франка - Вербицька, Л. (Літературознавчі обрії. Праці молодих учених, 2010)
Intercommunication of man and nature are considered in the article on the philosophical level, in the light of historical epochs, the scientific inheritance of Ivan Franko («Science and its mutual relations of working classes», «Opinions about the evolution of history of the humanity», «What is the advancement?»). It is analyzed from the point of view of the philosophical relations of the «man – nature» on the positivistic base, in the context of the philosophical relations in Ivan Franko’s scientific reception: God y nature y man y society.